Multiple chromosomal rearrangements structured the ancestral vertebrate Hox-bearing protochromosomes. - Vincent J Lynch; Günter P Wagner (PLoS Genetics, 2009)
While the proposal that large-scale genome expansions occurred early in vertebrate evolution is widely accepted, the exact mechanisms of the expansion--such as a single or multiple rounds of whole genome duplication, bloc chromosome duplications, large-scale individual gene duplications, or some combination of these--is unclear. Gene families with a single invertebrate member but four vertebrate members, such as the Hox clusters, provided early support for Ohno's hypothesis that two rounds of genome duplication (the 2R-model) occurred in the stem lineage of extant vertebrates. However, despite extensive study, the duplication history of the Hox clusters has remained unclear, calling into question its usefulness in resolving the role of large-scale gene or genome duplications in early vertebrates. Here, we present a phylogenetic analysis of the vertebrate Hox clusters and several linked genes (the Hox "paralogon") and show that different phylogenies are obtained for Dlx and Col genes than for Hox and ErbB genes. We show that these results are robust to errors in phylogenetic inference and suggest that these competing phylogenies can be resolved if two chromosomal crossover events occurred in the ancestral vertebrate. These results resolve conflicting data on the order of Hox gene duplications and the role of genome duplication in vertebrate evolution and suggest that a period of genome reorganization occurred after genome duplications in early vertebrates.